Liposomal Nanotraps Neutralize Listeria monocytogenes Toxins to Enhance Macrophage Viability and Antibacterial Capacity - Hervé Besançon; Margherita Polidori; Andrea Hostettler; Victor Nizet; Anna Oevermann; Eduard Babiychuk (Infectious Microbes & Diseases, 2025)
Abstract. Listeria monocytogenes is a human and veterinary pathogen, one of the most common agents of foodborne infections worldwide. It can cause severe complications such as meningitis or miscarriage. Antivirulence therapies, which target virulence factors such as pore-forming toxins, offer an alternative approach to combating infections. In this study, cholesterol-containing liposomal nanotraps effectively neutralized L. monocytogenes exotoxins, particularly listeriolysin O, thereby protecting mammalian cells. Notably, toxin neutralization was observed under both neutral and acidic conditions, where listeriolysin O activity is optimized to facilitate bacterial escape from the phagosome. Liposomal nanotraps were phagocytosed by macrophages and colocalized with intracellular Listeria, increasing the clearance rate of intracellular bacteria. These findings expand the potential use of broad-spectrum liposomal nanotrap therapy, which could be employed alongside current standard of care treatments to assist the immune system in controlling virulent pathogens.